Speech-Language Pathology in the Long-Term Care Setting: It Isn't Your Grandmother's Nursing Home Anymore - Casper, Mary L. (Seminars in Speech and Language, 2013)
This article considers the career of speech-language pathologists practicing in long-term care/skilled nursing facility settings. The range of conditions that lead to communication, cognition, and/or swallowing disorders that are evaluated and treated by the speech-language pathologist in the long-term care setting are examined. Various methodologies for reimbursement are discussed, including the Medicare Physicians' Fee Schedule associated with Medicare Part B and the Prospective Payment System associated with Medicare Part A. Suggestions for effective clinical service delivery are reviewed, along with best practices for interdisciplinary team communication.
Keywords: Skilled nursing facility; long-term care; Medicare; prospective payment; interdisciplinary team; communication; cognition; dysphagia